2010
DOI: 10.1103/physreve.82.056212
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of kicked particles in a double-barrier structure

Abstract: We study the classical and quantum dynamics of periodically kicked particles placed initially within an open double-barrier structure. This system does not obey the Kolmogorov-Arnold-Moser (KAM) theorem and displays chaotic dynamics. The phase-space features induced by non-KAM nature of the system lead to dynamical features such as the nonequilibrium steady state, classically induced saturation of energy growth and momentum filtering. We also comment on the experimental feasibility of this system as well as it… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…More recently, the seminal paper by Rigol et al [26] introduced the term ETH, pinpointed its importance for thermalization, and stimulated numerous, predominantly numerical studies on the validity of ETH for a large variety of specific models (mostly spin-chain-or Hubbard-like), initial conditions (often involving some quantum quench), and observables (mainly few-body or local), see e.g. [27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the seminal paper by Rigol et al [26] introduced the term ETH, pinpointed its importance for thermalization, and stimulated numerous, predominantly numerical studies on the validity of ETH for a large variety of specific models (mostly spin-chain-or Hubbard-like), initial conditions (often involving some quantum quench), and observables (mainly few-body or local), see e.g. [27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Suppose a particle follows a quasiperiodic orbit C 1 (μ 1 ) with winding number μ 1 before it encounters the boundary at x w and, emerges out in the region x > x w + b on an orbit C 2 (μ 2 ) with winding number μ 2 . It can be shown that as b → 0, μ 1 → μ 2 [9]. In this situation, trajectories of the particles crossing the double-barrier structure without suffering any reflection resemble the invariant tori of the corresponding standard map.…”
Section: Classical Dynamicsmentioning
confidence: 92%
“…In this section, we show that, if < 1, the presence of both the KAM-type and non-KAM type classical dynamical structures in the phase space leads to saturation of the mean energy of the system [9]. Though the complete arrest of energy growth can occur only as n → ∞, the time at which the energy growth effectively saturates is finite when measured in the units of T .…”
Section: Saturation Of Energy Growthmentioning
confidence: 97%
See 2 more Smart Citations